Broiler Chicken Production Performance with IoT-Based Semi-Closed House Management in Palaran District, Samarinda City, East Kalimantan: Performa Produksi Ayam Broiler dengan Manajemen Kandang Semi Closed House Berbasis Iot di Kecamatan Palaran, Kota Samarinda, Kalimantan Timur - Julinda Romauli Manullang; Yohanes Carlos Beda Ngama; Nurul Fajrih H; Anton (Buletin Peternakan Tropis, 2026)
Broiler chickens are one of the leading commodities in Indonesia’s poultry sector. They are known for their rapid growth and high feed-to-meat conversion efficiency. This study aims to analyze the production performance of broiler chickens in a semi-closed house system equipped with the Internet of Things (IoT) compared to a semi-closed house system without IoT. This study aims to analyze the production performance of broiler chickens in a semi-closed house system based on the Internet of Things (IoT) compared to a system without IoT. The research method involved direct observation in Palaran Subdistrict, Samarinda, over six rearing periods (three periods without IoT and three periods with IoT). A sample of 120 birds was randomly selected from a population of 6,000 to measure the variables of feed intake, body weight, mortality, Feed Conversion Ratio (FCR), and Performance Index (PI). The results showed that the use of IoT increased the average harvest weight from 1.67 kg to 1.98 kg and reduced the FCR from 1.59 to 1.52. Mortality initially spiked at the start of IoT implementation (9.45%) due to the system’s adaptation phase, but this figure was successfully reduced to 1.93% by the final period. Overall, the average PI increased significantly by 32.7%, from the “Poor” category (266.7) to the “Very Good” category (354.0). The implementation of IoT technology in semi-closed-house poultry houses effectively improves feed efficiency and broiler production performance after the adaptation phase.